Biblical Anthroponyms in Secular Contexts - Schochenmaier , Eugen (Onomástica desde América Latina, 2024)
The dossier on biblical anthroponyms in secular contexts offers an in-depth exploration of how biblical names transcend their religious origins to become integral elements of various cultural and linguistic landscapes. Through an interdisciplinary approach encompassing onomastics, socio-pragmatics, and cultural studies, the reviewed articles collectively underscore the enduring relevance and adaptability of biblical names. The studies reveal that these names have been integrated into everyday language and cultural practices, reflecting broader sociopolitical and cultural shifts. In Cuba, the persistence and adaptation of names like José, Juan, Pedro, and Rafael highlight their significance in shaping cultural identities amidst historical changes. Similarly, in Algeria and Israel, the phonetic adaptations and symbolic meanings of biblical names illustrate the complex interplay between historical, cultural, and religious influences. The studies on Mexico and Ukraine further emphasize the role of these names as markers of cultural continuity and identity, transcending their original religious connotations. Despite the comprehensive insights provided, several limitations were identified across the reviewed articles. Geographically, many studies focus on specific regions, limiting the generalizability of their findings. Temporally, the narrow scope of some studies based on specific periods may not capture long-term trends. There is a notable gender imbalance with a greater focus on male names, potentially overlooking gender-specific trends. An over-reliance on specific theoretical frameworks and secondary data sources may introduce biases, limiting the consideration of other perspectives. To address these gaps, future research should expand geographic and temporal scopes, ensuring a more comprehensive understanding of naming practices. Diversifying theoretical frameworks and incorporating comparative studies with other cultural contexts will offer broader insights. Detailed phonetic and pragmatic analyses, along with the use of visual aids, will enhance accessibility and richness of findings. Lastly, discussing the broader implications of these findings for other languages and cultural contexts will enhance the relevance and impact of the research. This comprehensive approach will enrich the field of onomastics and contribute to a deeper understanding of the dynamic interplay between religious heritage and secular adaptation of biblical names.